La influencia del branding en el posicionamiento de una marca de cerveza importada en Lima Metropolitana - Huaraca Cabrera, Ruth María (2023)
The purpose of this study is to measure the influence of Corona Extra beer’s branding on its positioning in Lima Metropolitana. Likewise, three specific objectives were set for the research: to measure the influence of brand awareness, brand image and the development of the Brand building blocks for Corona beer’s brand positioning in Lima Metropolitana. A non-experimental, quantitative, descriptive-correlational research design was carried out, using the survey technique and the questionnaire instrument. In this way, a sample of 271 people between 18 and 55 years of age, belonging to socioeconomic levels A, B and C residing in Lima Metropolitana was obtained. The results were processed in computer programs such as Microsoft Excel and IBM SPSS, in order to validate the hypotheses and analyze the data obtained. The findings show that branding greatly influences the brand positioning of Corona beer in Lima Metropolitana and that brand awareness, brand image and the development of brand building blocks greatly influence the brand positioning of Corona beer in Lima Metropolitana.